A CONSENSUS ON RISK MITIGATION FOR BROLUCIZUMAB IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION: Patient Selection, Evaluation, and Treatment. Issue 9 (13th September 2022) - Holz, Frank G.; Iida, Tomohiro; Maruko, Ichiro; Sadda, SriniVas R.
Abstract : This report provides guidance on the use of brolucizumab for neovascular age-related macular degeneration, given the events of retinal vascular occlusion associated with brolucizumab. Benefit–risk assessment, patient education, and evaluation for inflammation before injection are important components of treatment of neovascular age-related macular degeneration with brolucizumab. Abstract : Purpose: Brolucizumab has high efficacy in retinal fluid resolution and provides the possibility for longer dosing intervals in the treatment of neovascular age-related macular degeneration. However, brolucizumab has been associated with events of retinal vasculitis and retinal vascular occlusion typically in the presence of other signs of intraocular inflammation (IOI). The purpose of this report is to provide guidance on the use of brolucizumab for neovascular age-related macular degeneration to a global audience. Methods: A literature review was conducted on adverse events related to IOI after administration of brolucizumab in eyes with neovascular age-related macular degeneration. Results: Possible risk factors for IOI and retinal vascular occlusion after brolucizumab should be considered before administering brolucizumab. Patients who receive brolucizumab should be educated on the symptoms, signs, and time course of IOI after brolucizumab. Before each injection of brolucizumab, physicians should assess the eye for any signs of inflammation and not treat with brolucizumab if inflammation is detected. Treatment of IOI should be prompt and provided with particular attention to the posterior segment. Conclusion: Careful patient selection, patient education, assessment for inflammation, and intensive treatment of possible inflammation are important when using brolucizumab in patients with neovascular age-related macular degeneration.